Diriliş Sonrası Siklusu İçerisinde İki Sahne: Emmaus Yolunda ve Emmaus’da Akşam Yemeği - Demi̇r, Hatice (Istanbul University, 2021)
This study examines scenes from two important 14th-century tableaus depicting Christ with his disciples: On the Road to Emmaus and the Supper at Emmaus. While such portrayals of the post-Resurrection cycle were rare in Eastern/Byzantine art, they were far more prevalent in Western/Latin art. The earliest example of On the Road to Emmaus in Eastern art is at the Basilica of Ravenna Sant’Apollinare Nuovo, dating to the 6th century. The earliest instance in Western art is a 9th-century depiction on an ivory plaque. Latin samples of the scenes are popular in illustrated manuscripts. The study scope can be divided into two parts. The first part examines Eastern/Byzantine examples and the second part analyzes Western/Latin samples per a hierarchical classification. In the conclusion and evaluation section, the selected examples are compared. Eastern examples of the two scenes are rare and quantitatively outnumbered in Western/Latin art. This study explores the reasons for the rareness of these scenes in Eastern art and their abundance in Western art; different interpretations of the same are presented in the conclusion. Finally, the iconography of the two scenes differs in Eastern and Western examples. Therefore, our evaluation is focused on solving these questions. Our primary aim was to answer these problematic questions on the sources and reasons for the differences in iconography. The selection of the Byzantine and Latin samples was limited to those from the end of the 14th century to evaluate them in their synchronicity.
Keywords: Emmaus Road; Supper; Post-Resurrection; Christ; Byzantine Painting; Emmaus Yolu; Akşam Yemeği; Diriliş Sonrası; İsa; Resim; 16. Peace & justice